Frequency multiplexed photothermal correlation tomography for non-destructive evaluation of manufactured materials - Pengfei Zhu; Rongbang Wang; Koneswaran Sivagurunathan; Stefano Sfarra; Fabrizio Sarasini; Clemente Ibarra-Castanedo; Xavier Maldague; Hai Zhang; Andreas Mandelis (International Journal of Extreme Manufacturing)
Infrared thermography has been widely applied in real industrial inspection of aerospace, energy management systems, engines, and electric systems. However, two-dimensional imaging modality limits its development. Here, a technique named frequency multiplexed photothermal correlation tomography (FM-PCT) was developed to enable non-destructive and contactless cross-sectional imaging for manufactured material evaluation and characterization. By combining advantages of photothermal tomography and pulsed thermography, FM-PCT facilitates the generation of three-dimensional thermal images through temporal superposition (stacking) of two-dimensional images from sequential subsurface depths. FM-PCT image processing involves pulsed excitation signals to which frequency delay and matched filtering techniques are applied. Major features of FM-PCT are high-resolution three-dimensional tomographic imaging under low camera frame-rate conditions with self-correcting capability for diffusion (blurring) correction of subsurface images due to cross-correlation processing of individual frequencies in the Fourier decomposition spectrum of the excitation pulse. Furthermore, FM-PCT extends truncated-correlation photothermal coherence tomography from chirp and pulsed signals to more general linear heating sources. Lock-in thermography and x-ray computed tomography validation demonstrate that 3D FM-PCT imaging accurately reveals subsurface discontinuities/defects in solids despite the diffusive nature of thermal-wave imaging.